Analysis of the Distribution of Suspended Sediments at High and Low Tides in Nambo Coastal Waters, Kendari City - Hasmawati, Hasmawati; Irawati, Irawati; Haraty, Syamsul Razak (Faculty of Fisheries and Marine, Universitas Riau, 2023)
This research aims to determine the concentration of TSS distribution water quality characteristics and map the distribution of TSS in the waters of Nambo Beach. Determination of research stations used a purposive sampling method consisting of 7 stations. Water samples were taken at high tide and low tide using sample bottles. The method used in this research is a quantitative method and laboratory analysis to determine the TSS value. The method used to analyze TSS samples is the gravimetric method. The research results show that the distribution of TSS at high tide ranges between 21.80-122.00 mg/L, with the highest TSS value at stations 1-2, while the lowest value is at station 4, namely 21.80 mg/L. The TSS value at low tide ranges from 13.20-19.90 mg/L.